Circulating Donor Lung-specific Exosome Profiles Enable Noninvasive Monitoring of Acute Rejection in a Rodent Orthotopic Lung Transplantation Model. Issue 4 (14th May 2021) - Habertheuer, Andreas; Ram, Chirag; Schmierer, Maggie; Chatterjee, Shampa; Hu, Robert; Freas, Andrew; Zielinski, Patrick; Rogers, Wade; Silvestro, Eva M.; McGrane, Michael; Moore, Jonni S.; Korutla, Laxminarayana; et al.
Abstract : Background: There is a critical need for development of biomarkers to noninvasively monitor for lung transplant rejection. We investigated the potential of circulating donor lung-specific exosome profiles for time-sensitive diagnosis of acute rejection in a rat orthotopic lung transplant model. Methods: Left lungs from Wistar transgenic rats expressing human CD63-GFP, an exosome marker, were transplanted into fully MHC-mismatched Lewis recipients or syngeneic controls. Recipient blood was collected between 4 h and 10 d after transplantation, and plasma was processed for exosome isolation by size exclusion column chromatography and ultracentrifugation. Circulating donor exosomes were profiled using antihuman CD63 antibody quantum dot on the nanoparticle detector and via GFP trigger on the nanoparticle flow cytometer. Results: In syngeneic controls, steady-state levels of circulating donor exosomes were detected at all posttransplant time points. Allogeneic grafts lost perfusion by day 8, consistent with acute rejection. Levels of circulating donor exosomes peaked on day 1, decreased significantly by day 2, and then reached baseline levels by day 3. Notably, decrease in peripheral donor exosome levels occurred before grafts had histological evidence of acute rejection. Conclusions: Circulating donor lung-specific exosome profiles enable an early detection of acute rejection before histologic manifestation of injury to the pulmonary allograft. As acute rejection episodes are a major risk factor for the development of chronic lung allograft dysfunction, this biomarker may provide a novel noninvasive diagnostic platform that can translate into earlier therapeutic intervention for lung transplant patients.